2012
DOI: 10.2215/cjn.03880412
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking with Cardiovascular and Infection-Related Morbidity and Mortality in Chronic Hemodialysis

Abstract: SummaryBackground and objectives Smoking is common in the hemodialysis population and is associated with increased all-cause mortality and development of cardiovascular disease. Cause-specific outcomes have not yet been examined in detail. This study investigated the association of baseline smoking status with all-cause, cardiovascular, and infection-related morbidity and mortality in patients undergoing long-term hemodialysis.Design, setting, participants, & measurements Post hoc analysis of the HEMO Study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Natural killer cells and immunoglobulin (IgA, IgG, and IgM) levels are also reduced in smokers, which will reduce immune threshold further [ 71 73 ]. Tobacco use is an independent predictor of all-cause and infection-related mortality in hemodialysis patients [ 74 , 75 ]. Keeping these factors in mind, kidney transplant recipients with reduced immunity will be at more risk of developing infections.…”
Section: Cigarette Smoking and Kidney Recipientmentioning
confidence: 99%
“…Natural killer cells and immunoglobulin (IgA, IgG, and IgM) levels are also reduced in smokers, which will reduce immune threshold further [ 71 73 ]. Tobacco use is an independent predictor of all-cause and infection-related mortality in hemodialysis patients [ 74 , 75 ]. Keeping these factors in mind, kidney transplant recipients with reduced immunity will be at more risk of developing infections.…”
Section: Cigarette Smoking and Kidney Recipientmentioning
confidence: 99%
“…There are limited studies in the literature that have explored the relationship of smoking with clinical outcomes among incident dialysis cohorts. While, previous studies have demonstrated that smoking is associated with adverse clinical outcomes, most of these have considered smoking as an adjustment variable rather than the primary exposure [ 10 15 ]. Furthermore, to our knowledge, only a single published study has explored risks of smoking among dialysis patients with pre-existing atherosclerotic disease [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current body of evidence would suggest that tobacco use is an independent predictor of all-cause and infection-related mortality [ 11 , 13 15 ] and de-novo vascular disease [ 10 ]. However, it has been unclear until now the extent to which smoking contributes to death and transplantation in men and in women with atherosclerotic disease and across different age categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, observational studies have documented a higher cardiovascular mortality and hospitalization rate in hemodialysis patients who were current smokers than patients who never smoked, with intermediate rates seen in former smokers. 30 Statins consistently reduce cardiovascular events in the general population in both primary and secondary prevention. 31 The frequency of cardiac events is far greater in dialysis patients than the general population, which might translate into an enormous benefit of statins.…”
Section: Medical Management Of Coronary Artery Diseasementioning
confidence: 99%